ADAPTATION OF INTERNET ETHICAL ATTITUDE SCALE TO UNIVERSITY STUDENTS: COMPARISON OF INTERNET ETHICAL ATTITUDES ACCORDING TO STUDENTS’ DEPARTMENTS - Aynur Gecer; Nilgun Tosun (European Scientific Journal, ESJ, 2015)
Internet ethics is clearly an issue that concerns every Internet user closely no matter what their purpose is. Teachers are undoubtedly the ones to assume the most critical task at this stage. As persons who will shape future generations, teachers are expected to fully grasp the importance of Internet ethics in school years and display model behavior using the Internet fairly. The goal of this study is to adapt the Internet ethical attitude scale for students from secondary school to university and compare the ethical attitudes of participant students according to their genders and departments. The study was carried out with 294 students. The data was collected through the Internet Ethical Attitude Scale (IEAS) and personal information form designed by researchers. The results showed that female students had higher total scores and sub-factor scores in IEAS than male students. It is possible to say that female students are more conscientious than male students in the issue of Internet ethical attitudes. As in other factors, attitudes related to “homework plagiarism” are higher in female students than male students.